2001
DOI: 10.1017/s1355617701777065
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral deficits associated with chronic fatigue syndrome in veterans with Gulf War unexplained illnesses

Abstract: Gulf War unexplained illnesses (GWUI) are a heterogeneous collection of symptoms of unknown origin known to be more common among veterans of the Gulf War than among nonveterans. In the present study we focused on one of these unexplained illnesses. We tested the hypothesis that in a sample of Persian Gulf War veterans chronic fatigue syndrome (CFS) was associated with cognitive deficits on computerized cognitive testing after controlling for the effects of premorbid cognitive differences. We obtained A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Regression analyses also demonstrated poorer retention in association with subjective memory complaints. These results contrast with previous research (Binder et al, 2001; White et al, 2001) that did not find a connection between subjective complaints and objective impairment. Chao (2017) concluded that subjective memory complaints are sensitive to neuropsychological deficits and, as subjective memory complaints are linked to dementia risk, a necessary component of GW neuropsychological assessment.…”
Section: Subjective Memorycontrasting
confidence: 99%
See 1 more Smart Citation
“…Regression analyses also demonstrated poorer retention in association with subjective memory complaints. These results contrast with previous research (Binder et al, 2001; White et al, 2001) that did not find a connection between subjective complaints and objective impairment. Chao (2017) concluded that subjective memory complaints are sensitive to neuropsychological deficits and, as subjective memory complaints are linked to dementia risk, a necessary component of GW neuropsychological assessment.…”
Section: Subjective Memorycontrasting
confidence: 99%
“…Binder et al (2001) investigated cognitive performance in symptomatic GW veterans ( n = 94) as defined by chronic fatigue syndrome (CFS). Groups were divided based on CFS criteria (Fukuda et al, 1994) with 32 participants comprising the case group and 62 participants comprising the control group.…”
Section: Symptomatic Vs Non-symptomatic Deployed Gw Veterans and Neumentioning
confidence: 99%
“…Despite significant challenges, human testing for the neurotoxic effects of occupational exposures to chemicals is steadily advancing (104)(105)(106)(107). These procedures have also been used to examine the neurotoxic effects of the stress and hazards of war (108,109), which demonstrates broadening utility and acceptance of these testing procedures. The World Health Organization (WHO) recommended a neurobehavioral test battery for humans (110) and test batteries for assessing children (111).…”
Section: Human and Animal Assessment Of Learning And Developmentmentioning
confidence: 99%
“…The Portland Environmental Hazards Research Centre published a series of studies that built on each other as their cohort of GW veterans from the US Pacific Northwest grew (Anger et al 1999;Storzbach et al 2000;Binder et al 2001;Storzbach et al 2001). The neuropsychological studies sampled for symptomatic and asymptomatic subgroups, which were based on health survey responses combined with clinical examinations that permitted exclusion of medically explainable health symptoms.…”
Section: Performance-based Neuropsycholo-gical Outcomes Of Gw Deploymentmentioning
confidence: 99%
“…However, Gulf-and Germany-deployed participants did not differ on the TOMM, and rates of clinically significant sub-optimal performances were extremely low in both groups. Similarly, although the Portland group consistently found GW veterans with high-symptom complaints to perform more poorly than healthy controls on a forced-choice test of motivation, attention and memory (the Oregon Dual Task Procedure; Anger et al 1999;Binder et al 2001), performances fell within the range of adequate effort, and group differences were interpreted to reflect impairment of cognitive processes other than effort. Thus, when findings are taken together, insufficient effort does not appear to explain neuropsychological deficits in GW veterans.…”
Section: Performance-based Neuropsycholo-gical Outcomes Of Gw Deploymentmentioning
confidence: 99%